Knowledge, attitude and practice towards physical activity among healthcare students at a public university in Saudi Arabia - Kandasamy, Geetha; Almanasef, Mona; Almeleebia, Tahani; Orayj, Khalid; Viswanath Reddy, Lingala Kalyan; Shorog, Eman; Alshahrani, Asma M.; Prabahar, Kousalya; Veeramani, Vinoth Prabhu; Amirthalingam, Palanisamy; Alqifari, Saleh F.; Vasudevan, Rajalakshimi; et al. (Frontiers in Public Health, 2024)
This research aimed to study the knowledge, attitudes, and practices (KAP) towards physical activity (PA) of healthcare students at King Khalid University in Abha, Saudi Arabia.A prospective web-based cross-sectional study was carried out among healthcare students of King Khalid University from March to May 2024. Out of the 383 participants, 175 (45.7%) were men and 208 (54.3%) were women. Most of the students, 292 (76.2%), had a body mass index (BMI) of 18.5 to 24.9. Among the 383, 264 (68.9%) showed good knowledge, 288 (75.2%) had positive attitudes, and 242 (63.2%) had satisfactory PA practice. Most of them, 310 (80.9%), were aware that "regular exercise helps promote strong bones and muscles". 352 (91.9%) students believed that individuals who frequently engaged in PA had longer lifespans. More than half of the students (n=239, 62.4%) engaged in the recommended level of PA. Of the students, 179 (46.8%) agreed that they planned to begin increasing their physical activity during the next six months. 156 (40.7%) stated that they did sports with a high level of intensity for 20 minutes, three to five times a week, and 175 (45.7%) stated that they did moderate-intensity sports for 30 minutes, more than five times a week. None of the independent variables had a significant effect on good knowledge levels (P > 0.05). The regression results show being male OR=0.473 (CI 0.285 to 0.783 P=0.004), and being a first-or third-year student OR=0.329 (CI 0.130 to 0.832 P=0.013), OR=0.276 (CI 0.100 to 0.762 P=0.019) has a significant effect on positive attitude levels, while being male OR=1.945 ( CI 1.207 to 3.135 P=0.006) and having a BMI between 18.5 and 24.9 OR= 10.101 (CI 2.104 to 48.49 P=0.004) has a significant effect on satisfactory practice levels.The majority of participants in our study showed good knowledge and positive attitudes toward PA. A lower number of participants, though still the majority, had satisfactory levels of PA. Health education and health promotion initiatives should maintain and enhance knowledge of the positive effects of PA on health.